Bangladesh: successes in the fight against Islamist militancy ; democracy and the rule of law as a bulwark against radicalism - Lorch, Jasmin (SWP Comments, 2011)
After Bangladesh's return to democracy, the world's third-largest Muslim-majority country continues to be faced with tendencies of Islamist militancy. In the last two years, however, the government and the judiciary have achieved remarkable successes in three areas: The High Court has strengthened the secular legal system by banning punishment under fatwa. A special tribunal has been established for the prosecution of war crimes committed by Islamists during the Bangladesh Liberation War of 1971. And the government has had numerous members of terrorist organizations arrested. Bangladesh provides an example that Islam and democracy can be reconciled. In the fight against Islamist militancy, the country relies mainly on measures grounded in the rule of law